Judicial Preclusion in International Arbitration: Comparative Analysis of UK, Australia, and Malaysia’s Practices - Che Rosli, Iyllyana; Ghouri, Ahmad; Ghapa, Norhasliza; Zakariah, Asril Amirul; Kamariah Musa, Murshamsul (Faculty of Law, Jambi University, 2024)
This paper examines the issue of judicial preclusion in international arbitration, focusing on whether an award-debtor’s failure to challenge a foreign award at the supervisory court precludes them from contesting the enforcement of an award in another jurisdiction. Through a comparative analysis of judicial practices in the United Kingdom, Australia, and Malaysia, the study evaluates the extent of harmonisation in the application of Article V of the Convention on the Recognition and Enforcement of Foreign Arbitral Awards 1958 (NYC 1958). The findings reveal divergences: while UK and Australian courts adopt a flexible approach, allowing enforcement-stage challenges irrespective of prior actions at the supervisory court, Malaysian courts demonstrate a strong pro-enforcement bias, often deferring to the decisions of the supervisory court and restricting opportunities for re-litigation. This paper engages with the theories of res judicata and finality, exploring their interplay with judicial discretion and highlighting the tension between fairness and the finality of arbitration awards. It concludes with critical recommendations for enhancing harmonisation under the NYC 1958, including clearer guidelines on judicial preclusion, the integration of international best practices, and reforms to balance enforcement predictability and certainty in international arbitration